The effects of curcumin supplementation on oxidative stress, Sirtuin-1 and peroxisome proliferator activated receptor γ coactivator 1α gene expression in polycystic ovarian syndrome (PCOS) patients: A randomized placebo-controlled clinical trial. Issue 2 (March 2020) - Heshmati, Javad; Golab, Fereshteh; Morvaridzadeh, Mojgan; Potter, Eric; Akbari-Fakhrabadi, Maryam; Farsi, Farnaz; Tanbakooei, Sara; Shidfar, Farzad
Abstract: Background & aims: Curcumin is a biologically active phytochemical ingredient found in turmeric and has antioxidant pharmacologic actions that may benefit patients with polycystic ovarian syndrome (PCOS). The aim in this trial was to evaluate the efficacy of curcumin supplementation on oxidative stress enzymes, sirtuin-1 (SIRT1) and Peroxisome proliferator activated receptor γ coactivator 1α (PGC1α) gene expression in PCOS patients. Methods: Seventy-two patients with PCOS were recruited for this randomized, double-blinded, clinical trial. Thirty-six patients received curcumin, 1500 mg (three times per day), and 36 patients received placebo for 3 months. Gene expression of SIRT1, PGC1α and serum activity of glutathione peroxidase (Gpx) and superoxide dismutase (SOD) enzymes were evaluated at the beginning of trial and at 3-month follow-up. Results: Sixty-seven patients with PCOS completed the trial. Curcumin supplementation significantly increased gene expression of PGC1α ( p = 0.011) and activity of the Gpx enzyme ( p = 0.045). Curcumin also non-significantly increased gene expression of SIRT1 and activity of the SOD enzyme. Conclusions: Curcumin seems to be an efficient reducer of oxidative stress related complications in patients with PCOS. Further studies on curcumin should strengthen our findings. Highlights: Polycystic ovary syndrome (PCOS) is a common gynecological disease. Oxidative stress and imbalance between oxidants and antioxidants correlate with PCOS complications. Curcumin is a potent antioxidant in turmeric and it has been proved to impact the expression of antioxidant related genes. Curcumin can improve body antioxidant enzymes by impacting related gene expression in patients with PCOS.